Improved Synthesis of Unsymmetrical Ureas via Carbamates - Prachi, Ramteke; Tanwar, Dinesh Kumar; Gill, Manjinder Singh (SynOpen, 2023)
An efficient, cost-effective, easy and green method is reported for the preparation of N,N′-alkyl aryl ureas and N,N′-dialkylureas via carbamates. This improved procedure is devoid of any hazardous reagents such as phosgene and isocyanates, and shows broad substrate scope with good to excellent yields. As compared to previous reports, this procedure offers an operationally simple, potentially scalable, and, significantly, benign way to synthesize these important urea motifs.
Keywords: carbamates; ureas; unsymmetrical ureas; amine; scale-up; organic synthesis